Preoperative cross functional teams improve OR performance. Issue 3 (18th May 2015) - Bitter, Justin; van Veen-Berkx, Elizabeth; van Amelsvoort, Pierre; Gooszen, Hein
Abstract : Purpose: – The purpose of this paper is to present the effect of the introduction of cross-functional team (CFT)-based organization, rather than, on planning and performance of OR teams. Design/methodology/approach: – In total, two surgical departments of the Radboud University Nijmegen Medical Center (RUNMC) in the Netherlands were selected to illustrate the effect on performance. Data were available for a total of seven consecutive years from 2005 until 2012 and consisted of 4, 046 OR days for surgical Department A and 1, 154 OR days for surgical Department B on which, respectively 8, 419 and 5, 295 surgical cases were performed. The performance indicator "raw utilization" of the two surgical Departments was presented as box-and-whisker plots per year (2005-2011). The relationship between raw utilization ( y ) and years ( x ) was analyzed with linear regression analysis, to observe if performance changed over time. Findings: – Based on the linear regression analysis, raw utilization of surgical Department A showed a statistically significant increase since 2006. The variation in raw utilization reduced from IQR 33 percent in 2005 to IQR 8 percent in 2011. Surgical Department B showed that raw utilization increased since 2005. The variation in raw utilization reduced from IQR 21 percent in 2005 to IQR 8 percent in 2011. Social implications: – Hospitals need to improve their productivity and efficiency in response to higher societal demands and rapidly escalating costs. The RUNMC increased their OR performance significantly by introduction of CFT-based organization in the operative process and abandoning the so called functional silos. Originality/value: – The stepwise reduction of variation – a decrease of IQR during the years – indicates an organizational learning effect. This study demonstrates that introducing CFTs improve OR performance by working together as a team.